Antibody-Conjugated Nanoparticles for Biomedical Applications. (3rd December 2009) - Arruebo, Manuel; Valladares, Mónica; González-Fernández, África
Abstract : Nanoscience and Nanotechnology have found their way into the fields of Biotechnology and Medicine. Nanoparticles by themselves offer specific physicochemical properties that they do not exhibit in bulk form, where materials show constant physical properties regardless of size. Antibodies are nanosize biological products that are part of the specific immune system. In addition to their own properties as pathogens or toxin neutralizers, as well as in the recruitment of immune elements (complement, improving phagocytosis, cytotoxicity antibody dependent by natural killer cells, etc.), they could carry several elements (toxins, drugs, fluorochroms, or even nanoparticles, etc.) and be used in several diagnostic procedures, or even in therapy to destroy a specific target. The conjugation of antibodies to nanoparticles can generate a product that combines the properties of both. For example, they can combine the small size of nanoparticles and their special thermal, imaging, drug carrier, or magnetic characteristics with the abilities of antibodies, such as specific and selective recognition. The hybrid product will show versatility and specificity. In this review, we analyse both antibodies and nanoparticles, focusing especially on the recent developments for antibody-conjugated nanoparticles, offering the researcher an overview of the different applications and possibilities of these hybrid carriers.